Groundwater quality assessment of Labuan Island - Moayedi, Hossein; Kim Huat, Bujang; Asadi, Afshin; Kazemian, Sina; Mohammad Ali, Thamer Ahmad (Academic Journals, 2011)
Groundwater is known as an important source of water supply due to its relatively low susceptibility to pollution in comparison to surface water, and its large storage capacity (USEPA, 1985). It should be mentioned that water pollution is any physical, chemical or biological change in the quality of water that has a harmful effect on any living thing that drinks, uses or lives in it. When humans drink polluted water, it often has serious effects on their health. Water pollution can also make water unsuitable for the desired use. In the present research, different water quality parameters were observed from the different monitoring wells through the Labuan Island. Then by interpolation between the available data, the maps of the different water quality parameters were observed. Each map was classified based on the Malaysia water quality standard, and the results clearly showed those areas which are susceptible to groundwater contamination.